1994
DOI: 10.1210/jc.78.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and insulin resistance

Abstract: The associates of gout-obesity, hypertriglyceridemia, glucose intolerance, and hypertension, strikingly resemble those of insulin resistance. In the present study we determined whether hyperuricemia is associated with insulin resistance and, if so, whether this association can be explained by other components of the syndrome. For this purpose we quantitated insulin sensitivity (euglycemic clamp) in 37 nondiabetic subjects (aged 30-68 yr) exhibiting varying degrees of the metabolic syndrome (body mass index, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 0 publications
7
80
0
7
Order By: Relevance
“…In keeping with the latter, IR is inversely related to the urinary uric acid clearance and the latter is inversely related to SU concentrations 22. Indeed, SU may serve as a surrogate marker of IR 1. Although raised TG levels are a hallmark of IR9 and appear to exist intrinsically in gout,23 a low calorie diet in hyperuricaemic-hypertriglyceridaemic patients resulted in a reduction in serum TG concentrations together with an increased uric acid clearance and a decrease in SU levels, which did not occur in normolipidaemic-hyperuricaemic patients 24.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In keeping with the latter, IR is inversely related to the urinary uric acid clearance and the latter is inversely related to SU concentrations 22. Indeed, SU may serve as a surrogate marker of IR 1. Although raised TG levels are a hallmark of IR9 and appear to exist intrinsically in gout,23 a low calorie diet in hyperuricaemic-hypertriglyceridaemic patients resulted in a reduction in serum TG concentrations together with an increased uric acid clearance and a decrease in SU levels, which did not occur in normolipidaemic-hyperuricaemic patients 24.…”
Section: Discussionmentioning
confidence: 66%
“…Gout and the insulin resistance (IR) syndrome have several features in common 1. Insulin resistance is associated with obesity, hypertension, glucose intolerance, coronary artery disease (CAD), increased triglyceride (TG) levels, decreased high density lipoprotein cholesterol (HDL-C) concentrations, increased C:HDL-C ratios, low density lipoprotein cholesterol (LDL-C), and uric acid levels, and atherogenic small, dense LDL-C particles 2…”
mentioning
confidence: 99%
“…In contrast, type 2 diabetes and the metabolic syndrome are often associated with higher SUA concentrations [37, 38], although some studies have reported the presence of hypouricaemia in type 2 diabetes [39, 40]. The increase might be accounted for by the presence of insulin resistance and hyperinsulinaemia.…”
Section: Renal Handling Of Uric Acid In Patients With Diabetesmentioning
confidence: 99%
“…A high concentration of uric acid is closely related to hyperinsulinaemia, glucose intolerance, hypertension, dyslipidaemia, very high levels of triglycerides, low levels of high density lipoprotein (HDL) cholesterol, and obesity (especially abdominal adiposity). [4][5][6][7][8][9][10][11][12] Regarding the association that has already been demonstrated between hyperuricaemia and hyperlipidaemia, we have previously shown the existence of two groups of hyperuricaemic patients-those in whom the hyperuricaemia is associated with hyperlipidaemia, who could be considered to have the metabolic syndrome, and those having no association with any metabolic disorder. 13 We have also reported that hyperuricaemic-hypertriglyceridaemic patients have high levels of very low density lipoprotein (VLDL) components, a reduced fractionated excretion of uric acid, and an increased ratio of CIII to CII apolipoproteins.…”
mentioning
confidence: 99%